Metode Menghafal Dan Teknik Muraja’ah Di Pondok Pesantren Az Zainuriyah Dzarut Zakirot Cukir Jombang - Khumairoh An Nahdliyah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
This research aims to describe the methods of memorization for improving the ability of hafalan and murajaah techniques, as well as supportive and inhibiting factors in the implementation of the Qur'an hafalan in the Pondok Pesantren Az Zainuriyah Dzarut Dzakirot Cukir Jombang. This study uses qualitative methods with data collection techniques such as observations, interviews, and documentation. Data analysis uses data reduction, data presentation, and inference. The results of the research found that the methods used by the centurion in memorizing the Qur’an in the Pondok Pesantren Az Zainuriyah Dzarut Dzakirot are the Turkish methods of usmani, tasmi’, takrir, translation, analysis of nahwu shorof, bin nadzar, and bookah. As for the technique of muraja'ah used, it is tasmi', fami bisyauqin, khatamkan Al Qur'an bil ghoib at the time of prayer, tarawih, muraja’ah himself, and muraja‘ah deposited at the ustadzah. As for the supportive factors in remembering, they are self-motivation and the support of the nearest people, the presence of guided muroja’ah activities, the intelligence that each centri possesses, the existence of a taffidz diploma, and the conditions of the environment that are conducive. The inhibitory factors are laziness and saturation, health factors, absence of education, and too many other activities.